Earnings Expectations and Higher Education Enrolment Decisions in Hungary - Julia Varga (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2001)
This paper is based on a survey carried out among Hungarian secondary school students to examine (i) what students know about wages and relative wages when they are in their senior year of secondary school and are about to make decisions on their further studies (ii) how they form expectations regarding their future earnings and employment probabilities at different levels of schooling and (iii) whether their expectations of the labour market outcome of higher education have an impact on the probability of applying for higher educational studies. The results show that students on the average, have quite an accurate knowledge of current wages by educational levels and occupations. Their expected earnings are higher than their estimations of current earnings and their labour market return expectations have an impact on the probability of applying for further studies.
Keywords: 330